PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE - Suryani, Suryani (Universitas Budi Luhur, 2021)
This study aims to determine an effect of the variables of profitability, company size, sales growth, and audit quality on tax avoidance. Analyzing 12 samples of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2015 - 2019 period. The sample was selected based on the purposive sampling method and analyzed by multiple linear regression method using SPSS version 22 software. The results of this study indicate that Profitability and sales growth have a positive effect on tax avoidance, firm size has a negative effect on tax avoidance, while audit quality has no effect on tax avoidance.